Updating the Lamellar Hypothesis of Hippocampal Organization - Sloviter, Robert S.; Lømo, Terje (Frontiers in Neural Circuits, 2012)
In 1971, Andersen and colleagues proposed that excitatory activity in the entorhinal cortex propagates topographically to the dentate gyrus, and on through a “trisynaptic circuit” lying within transverse hippocampal “slices” or “lamellae” [Andersen, Bliss, and Skrede. 1971. Lamellar organization of hippocampal pathways. Exp Brain Res 13, 222-238]. In this way, a relatively simple structure might mediate complex functions in a manner analogous to the way independent piano keys can produce a nearly infinite variety of unique outputs. The lamellar hypothesis derives primary support from the “lamellar” distribution of dentate granule cell axons (the mossy fibers), which innervate dentate hilar neurons and area CA3 pyramidal cells and interneurons within the confines of a thin transverse hippocampal segment. Following the initial formulation of the lamellar hypothesis, anatomical studies revealed that unlike granule cells, hilar mossy cells, CA3 pyramidal cells, and Layer II entorhinal cells all form axonal projections that are more divergent along the longitudinal axis than the clearly “lamellar” mossy fiber pathway. The existence of pathways with “translamellar” distribution patterns has been interpreted, incorrectly in our view, as justifying outright rejection of the lamellar hypothesis [Amaral and Witter. 1989. The three-dimensional organization of the hippocampal formation: a review of anatomical data. Neuroscience 31, 571-591]. We suggest that the functional implications of longitudinally-projecting axons depend not on whether they exist, but on what they do. The observation that focal granule cell layer discharges normally inhibit, rather than excite, distant granule cells suggests that longitudinal axons in the dentate gyrus may mediate "lateral" inhibition and define lamellar function, rather than undermine it. In this review, we attempt a reconsideration of the evidence that most directly impacts the physiological concept of hippocampal lamellar organization.